Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV. (February 2023) - Fritz, D.; Danon, Y.; Rapp, M.; Trumbull, T.H.; Zerkle, M.; Holmes, J.; Chapman, C.W.; Arbanas, G.; Brown, J.M.; Ramic, K.; Hu, X.; Singh, S.; et al.
Abstract: Yttrium hydride serves as a neutron moderator material that enables compact, high temperature nuclear reactors. However, in order to accurately design and simulate a nuclear system relying upon yttrium hydride, the fundamental nuclear data of yttrium hydride must be well understood. Thermal neutron scattering law (TSL) evaluations represent an important aspect of nuclear data as thermal scattering can drastically alter the neutron multiplication factor of a system. Therefore, to support evaluation and validation of thermal neutron scattering for yttrium hydride, researchers at Rensselaer Polytechnic Institute (RPI) performed total thermal neutron cross section measurements for YH1.68 and YH1.85 over the energy range of 0.0005 - 3 eV. These measurements represent the first total cross section measurements for yttrium hydride that encompass the entire thermal region. Comparisons were made against the ENDF-B/VIII.0, Zerkle & Holmes and Oak Ridge National Laboratory TSL evaluations, where generally good agreement was found.